Internet of Things, Virtual Networks and the Economics of Shared Mobility - Günter Knieps (International Telecommunications Society (ITS), 2018)
In this paper the potentials for shared mobility services based on ICT innovations are charac-terized, requiring a paradigm shift from intramodal transportation markets to intermodal shared mobility markets. Heterogeneous ICT innovations are described, entailing various combinations of app-based mobile communications, (camera-based) sensor networks and big data processing. The potentials of shared mobility concepts to avoid traffic collapse and sig-nificantly reduce congestion and pollution in cities are considered, referring to different simu-lation studies on the impact of complete or partial replacement of private vehicles in a city with shared mobility services. Furthermore, the changing role of regulations in the context of the transition from traditional intramodal transportation markets to intermodal shared mobility services markets is considered. Firstly, it is necessary to abolish legal entry barriers to the lo-cal taxi market and the public transit market. Secondly, competition for subsidies of politi-cally desired non-cost covering (shared) mobility services should be symmetrical for all active and potential providers of shared mobility services. Thirdly, technical regulation and con-sumer protection including privacy and cybersecurity for the shared mobility markets should be applied symmetrically and consistently. Finally, the role of pilot projects to establish shared mobility concepts are demonstrated.
Keywords: 330